Unveiling hepatico-duodenal ligament lymphangioma in a sickle cell disease patient: A radiological and clinical case study - Viraj Gupta, MBBS; Ravishankar Patil, MD; Gaurav Mishra, MD; Pratapsingh H. Parihar, MD; Komal Mishra, MBBS; Gahana Kataria, MBBS; Rakshanda Agrawal, MBBS (Radiology Case Reports)
The 34-year-old female patient with sickle cell anemia had splenomegaly and excruciating stomach discomfort. radiological examinations showed a nonenhancing cystic lesion along the common bile duct, splenic infarcts, and a severely enlarged spleen with subcapsular calcifications, indicative of hepatoduodenal ligament lymphangioma. Minor ascites, borderline hepatomegaly, and a slight left-sided pleural effusion were among the related findings. The example highlights the clinical significance of sophisticated imaging techniques and the value of interdisciplinary care and thorough imaging in identifying uncommon illnesses and directing the right therapies.